Juvenile delinquencies in Malaysia: legal and social perspective / Wan Murshida Wan Hashim - Wan Hashim, Wan Murshida (University Publication Centre (UPENA), 2006)
Delinquent behaviour amongst the children becomes one of crucial issues in Malaysia. The delinquent act of a juvenile can either be the act or omission prohibited and punishable by law or act that is deliberate deviation from norm. Th ere are many aspects that involved in this issue and each of them should not be dealt separately. The legal and social aspects must go hand in hand in tackling the issue. This article discusses the legal framework as to the juvenile's criminal liability and the relationship between the social factors and the delinquent behaviours.